2019
DOI: 10.1016/j.ijpara.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the evolution and drug susceptibility of Babesia duncani from the sequence of its mitochondrial and apicoplast genomes

Abstract: Babesia microti and Babesia duncani are the main causative agents of human babesiosis in the United States. While significant knowledge about B. microti has been gained over the past few years, nothing is known about B. duncani biology, pathogenesis, mode of transmission or sensitivity to currently recommended therapies. Studies in immunocompetent wild type mice and hamsters have shown that unlike B. microti, infection with B. duncani results in severe pathology and ultimately death. The parasite factors invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 82 publications
3
19
0
Order By: Relevance
“…With the exception of B. conradae, piroplasm infective to the same host fell into one clade. These ndings are consistent with the phylogenetic position of B. gibsoni, B. duncani and B. orientalis based on the amino acid sequences of cox1 and cytb [26,27,30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With the exception of B. conradae, piroplasm infective to the same host fell into one clade. These ndings are consistent with the phylogenetic position of B. gibsoni, B. duncani and B. orientalis based on the amino acid sequences of cox1 and cytb [26,27,30].…”
Section: Discussionsupporting
confidence: 88%
“…Studies of mitochondrial genomes could provide new insight into the biological features, genetic evolution and classi cation of the causative agents, as well as providing data for designing anti-Babesia compounds. To date, sequencing of the mitochondrial genomes has been performed for B. bigemina, Babesia bovis, B. caballi, B. canis, B. conradae, B. duncani, B. gibsoni, B. microti, B. orientalis, B. rodhaini, B. rossi, B. vogeli, Theileria equi and T. orientalis [26][27][28][29][30][31]. However, there are limited data on the mitochondrial genomes of ovine Babesia spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, one pair of TIRs was found in the mitochondrial genomes of other Babesia spp. and Theileria spp., ranging from 25 to 1563 bp in length [ 26 28 , 30 , 32 ]. These findings indicated that the number and size of TIRs are one of the main causes of different mitochondrial genome sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we sequenced, assembled, annotated and characterized the apicoplast genome of B. gibsoni. The raw apicoplast genome sequence of B. gibsoni obtained from high throughput genome sequencing (data unpublished) was shown to have a circular form with a full length of 46 kb, which is bigger than that of any other reported Babesia apicoplast genome [22,23,[27][28][29]. To further verify the sequence, we adopted a primer-walking approach to test the B. gibsoni genomic DNA by designing a series of specific primers based on the amplicons covering the whole apicoplast genome (Additional file 1: Table S1, Additional file 2: Figure S1).…”
Section: Characteristics Of Apicoplast Genome Sequence Of B Gibsonimentioning
confidence: 90%